Dialogues de Paix. - Palais des Nations, Genève (Paris : l'Association Française d'Action Artistique, 1995)
Adeagbo, Georges ; Akpan, Sunday Jack ; Aldus, John ; Araeen, Rasheed ; Barthassat, Dominique ; Belkahia, Farid ; Ben Jr., Joe ; Bester, Willie ;Bethé Sélassié, Mickaël ; Bruly Bouabré, Frédéric ; Buren, Daniel ; Burki, Marie José ; Capelan, Carlos ; etc.
Dialogues de Paix / Dialogues of Peace, Palais des Nations, Genève, 03.07 - 24.10.1995
boek